UNDERAGE MARRIAGE AND ITS SOCIO-RELIGIOUS IMPACTS: A MAQĀṢID AL-SYARI‘AH CASE STUDY OF A SINGLE HOUSEHOLD IN WANAJAYA VILLAGE, BEKASI - Oyoh Bariah; Iwan Hermawan; Nur Aini Farida; Faras Afifah; Ikhsan Sayuti (Academic Bright Collaboration, 2026)
This study analyzes underage marriage in a single household in Wanajaya Village, Cibitung, Bekasi, through the lens of Maqāṣid al-Sharīʿah (the higher objectives of Islamic law). It aims to identify the socio-religious factors driving early marriage, assess its impacts on the individuals and family, and evaluate alignment between local practices and the five core Maqāṣid protections: religion, life, intellect, lineage, and wealth. A qualitative single-case study design was employed. Data were collected through semi-structured interviews, non-participant observation, and document review involving 6 participants from one household (underage married woman, her parents, husband, and sibling) and one religious leader in Wanajaya Village. Thematic analysis was guided by the Maqāṣid al-Sharīʿah framework. The underage marriage was conducted without court dispensation, facilitated by an unofficial payment to a KUA intermediary. Primary drivers included economic hardship, arranged matchmaking, and low parental education. The impacts – reproductive health concerns, psychological distress, educational truncation, economic vulnerability, and marital instability – violated four of the five Maqāṣid protections (life, intellect, lineage, wealth). The religious leader acknowledged that despite religious justifications, early marriage often leads to greater harm. The study is limited to a single household plus one religious leader, and is not statistically generalizable. Self-reported data may contain bias. Findings offer analytical insights into how procedural circumventions and narrow definitions of readiness contradict higher aims of Islamic law. Unlike prior quantitative or legal analyses, this study combines in-depth household-level fieldwork with a normative Maqāṣid-based critique, including the perspective of a village religious leader, revealing micro-level mechanisms and rationales that sustain underage marriage.